Basic science of cardiac contractility modulation therapy: Molecular and electrophysiological mechanisms - Masarone, Daniele; Kittleson, Michelle M.; D’Onofrio, Antonio; Falco, Luigi; Fumarulo, Isabella; Massetti, Massimo; Crea, Filippo; Aspromonte, Nadia; Pacileo, Giuseppe (Heart rhythm, 2024)
In heart failure with reduced ejection fraction and heart failure with preserved ejection fraction, profound cellular and molecular changes have recently been documented in the failing myocardium. These changes include altered calcium handling and metabolic efficiency of the cardiac myocyte, reactivation of the fetal gene program, changes in the electrophysiological properties of the heart, and accumulation of collagen (fibrosis) at the interstitial level. Cardiac contractility modulation therapy is an innovative device-based therapy currently approved for heart failure with reduced ejection fraction in patients with narrow QRS complex and under investigation for the treatment of heart failure with preserved ejection fraction. This therapy is based on the delivery of high-voltage biphasic electrical signals to the septal wall of the right ventricle during the absolute refractory period of the myocardium. At the cellular level, in patients with heart failure with reduced ejection fraction, cardiac contractility modulation therapy has been shown to restore calcium handling and improve the metabolic status of cardiac myocytes, reverse the heart failure–associated fetal gene program, and reduce the extent of interstitial fibrosis. This review summarizes the preclinical literature on the use of cardiac contractility modulation therapy in heart failure with reduced and preserved ejection fraction, correlating the molecular and electrophysiological effects with the clinical benefits demonstrated by this therapy. [Display omitted]